Charge layer optimized 4H-SiC SACM avalanche photodiode with low breakdown voltage and high gain. (4th October 2019) - Wu, Junkang; Zhang, Mingkun; Fu, Zhao; Hong, Rongdun; Zhang, Feng; Cai, Jiafa; Wu, Zhengyun
Abstract: An n-type charge layer was introduced into the 4H-SiC separated absorption and multiplication avalanche photodiode. The effect of the charge layer on the optoelectronic characteristics of the photodiode was modeled and studied to optimize the performance of the photodiode. According to the modeling results, 4H-SiC photodiodes were fabricated. A low breakdown voltage of 77.6 V and a significant gain of more than 10 5 were obtained. The peak responsivity for 270 nm illumination of the photodiode biased at −40 V was 83 mA W −1, corresponding to an external quantum efficiency over 38.2%. Both the simulated and experimental spectral responses are almost identical.